Parameters Selection for Enhanced Mechanical and Wear Properties of Natural Fiber Reinforced Hybrid Composites Using PSI Technique - P. Venkateshwar Reddy; R. Meenakshi Reddy; P. Srinivasa Rao; D. Mohana Krishnudu; R. V. Saikumar Reddy; A. Eswara Kumar (Journal of Natural Fibers, 2022)
Natural fibers are being used more often for composite preparation these days. Natural fiber-reinforced polymer composites have been used in a wide range of engineering domains due to their significant benefits over synthetic fiber composites. The interfacial interaction with the matrix content and water absorption are two main disadvantages of using natural fibers. The effects of natural fibers (Abutilon indicum, luffa cylindrica, and Prosopis juliflora), chemical treatments (NaOH, KOH, and silane), and fillers (CaCO3, Al2O3, and TiO2) on mechanical and wear properties were investigated in this study. The silane-treated fiber-reinforced composite outperformed the other two treatments and untreated fiber-reinforced composites in terms of mechanical properties. In the present study, multicriteria decision-making (MCDM) approaches were used to cope with the difficulty of choosing good estimate over a wide variety of opportunities. The predicted optimal combinations for good mechanical and wear outputs of the composite were chosen using a performance selection index (PSI) process. Characterizations such as FTIR and SEM are conducted to verify the applicability of hybrid composites in temperature, chemical, and humid environments. The bonding between the treated fibers and matrix strengthened with fiber treatment and filler addition, according to the SEM study.